Rare Case of Periampullary Duodenal Carcinoma - Maghfirah, Desi; Abubakar, Azzaki; Yusuf, Fauzi; Riswan, Muhammad (Majalah Kedokteran Bandung, 2021)
Periampullary carcinoma is a malignancy that appears around the vatteri ampulla. This malignancy can originate from the pancreas, duodenum, and distal choledochal duct. Duodenal cancer is a very rare case, only about 0.3% of the gastrointestinal malignancies. Reported cases are increasing with the increasing use of esophagogastroduodenoscopy. The most frequently found carcinomas of the duodenum include adenocarcinoma, carcinoid, lymphoma, and leiomyosarcoma. The symptoms of these carcinomas are often not specific so the diagnosis is often late, leading to a poor prognosis. Early diagnosis and proper therapy provide a good prognosis. The case reported here representeda 52-year-old woman presented with hematemesis melena, anemia, jaundice, epigastric mass, right hypochondrial pain, and weight loss. From the esophagogastroduodenoscopy, the mass was found to obstruct half of the duodenum lumen and bleeding, which was easily triggered, was observed in the second part of the duodenum. CT scan revealed a mass in the head of the pancreas with gall bladder hydrops and obstruction of the intra and extra-hepatic billier system. After a Whipple operation Laparotomy, the histology showed papillary adenocarcinoma duodenum. Patients then underwen chemotherapy with 5 fluorouracil regimen. Patient's clinical condition is currently improving and no complaint is conveyed by the patient.